Conceptual art patterns in cinema - Mohammed Akzar Maarij; Haider Faisal Karim (الاكاديمي)
The idea is the tool that makes art, as it rises above the form, so the work becomes a creative process like philosophy, determined by debate and the questioning. Here, the connection between the recipient and the function of art is broken, and the visual perception is employed with the senses, and freedom from the restrictions of formal craftsmanship is achieved, as the conceptual work goes beyond transforming reality and formulating it anew in artistic ways in absolute beauty. Therefore, reality is viewed as the primary field for aesthetic confrontation, i.e. containing a minimum of beauty, and transforming the work from content to concept, i.e. freedom from restrictions.